Green synthesis of zinc oxide nanoparticles using Atalantia monophylla leaf extracts: Characterization and antimicrobial analysis. (1st August 2018) - Vijayakumar, S.; Mahadevan, S.; Arulmozhi, P.; Sriram, S.; Praseetha, P.K.
Abstract: In the recent decades, nanotechnology has become an important research field of modern material science. Green synthesized nanoparticles have garnered wide interest due to its inherent features like rapidity, eco-friendly and cost-effectiveness. For the first time, Zinc Oxide nanoparticles were successfully synthesized using Atalantia monophylla leaf extract in the present's investigation. The biosynthesized Zinc Oxide nanoparticles were characterized by UV- Vis spectrophotometer, Fluorescence spectrometer (PL) and their peaks were identified to be at 352 and 410 nm respectively. The morphology of the Zinc Oxide nanoparticles was characterized by TEM with EDAX. The X- ray diffraction (XRD) studies showed the crystalline nature and revealed the purity of Zinc Oxide nanoparticles. FTIR spectroscopy was used to analyze the specific functional groups responsible for reduction, stabilization and capping agents present in the nanoparticles. The success-ability of bacteria and fungi with Synthesized ZnO nanoparticles tested using agar well diffusion method were discussed. The bacterial and fungal destruction was better for ZnO nanoparticles than reported for plant extracts and standard drugs. Thus this study proves that Zinc Oxide nanoparticles would contain natural anti-microbial agents through green synthesis which may serve for the production of drugs for antimicrobial therapeutics.